BIBLIOMETRIC REVIEW OF THE FOREST AS A TOOL FOR ENVIRONMENTAL EDUCATION - Ho, Tatiane Lima; Biondi, Daniela; Carlos Batista, Antonio; Martini, Angeline (Floresta, 2023)
The contact with the forest started in childhood enables the construction of values with nature. Bibliometric studies can help in the search for works on the forest theme. Thus, the objective of this work was to analyze the general panorama of scientific research on environmental education activities related to the forest, through bibliometric characterization in WoS and Scopus databases. The works were filtered from search codes that covered the theme. All articles were checked, and those that carried out environmental education activities and used the forest as a base were considered valid. The filtering resulted in 102 articles, of these, 62 articles it was possible to carry out a methodological analysis. Articles from 37 countries were found, with a greater number for the USA and 274 different authors, but the majority (93.4%) published only one manuscript. In the methodological analysis, most include non-formal teaching in specific environmental education activities. The forest in general is used for works focused on environmental perception and awareness, and the most used environmental interpretation techniques are field practices, in guided and self-guided interpretive trails. More than 50% of the articles do not justify the applied method and several works show methodological flaws that make it difficult to replicate the practices in other studies. It is concluded in the bibliometric analysis that there are a variety of authors talking about the subject, but a reference specialist author was not identified. The methodological flaws found prove the challenges of obtaining scientific advances in environmental education from the forest.